Along Navajo trails: recollections of a trader, 1898-1948 - Evans, Will, author; Woods, Susan E., editor; McPherson, Robert S., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
Will Evans was the proprietor of the Shiprock Trading Company in early 20th century New Mexico. Probably more than most of his fellow traders, he had a strong interest in Navajo culture. He published in the local newspaper and other periodicals and compiled many of his pieces into a book manuscript. His subjects were Navajos he knew and traded with, their stories of historic events such as the Long Walk, and descriptions of their culture as he, an outsider without academic training, understood it.
Will Evans, trader to the Navajos -- Starting along the trail -- Views of history around the Four Corners -- Agapito remembers the old days -- Yellow Horse and the Long Walk -- The establishment of trading posts -- Harry Baldwin and the Hogback Post -- Redrock Trading Post -- Little Singer and the beautiful mountain uprising -- Prosperity in reverse -- Oil and gas on Navajo land -- A Christmas Eve in Navajo land -- Navajos I have known -- Costiano -- Black Horse -- Bizhóshí -- Ugly Man -- Fat One and Son of Fat One -- Faith, an episode -- Tragedies in Navajo land -- Sandoval -- Slim policeman -- A dedicated medicine man -- Dan Pete -- Daily life and customs of the Navajo people -- Daily life in a hogan -- Navajo hospitality -- Trading with the Navajos -- Navajo blankets -- Silversmithing -- Cleanliness, clothes, and manners -- Hairstyles -- Tobacco, alcohol, and morality -- Navajo marriage customs and family life -- Divorce -- Tribal traditions and lore -- Sandpaintings -- My first fire dance -- Squaw dance (enemyway) -- Death, witchcraft, and skinwalkers -- Navajos and animals -- Postscript: The death of a man, the end of an era.
Keywords: Navajo Indians -- New Mexico -- Shiprock Region -- History; Navajo Indians -- New Mexico -- Shiprock Region -- Social life and customs; Navajo weavers -- New Mexico -- Shiprock Region -- History; Trading posts -- New Mexico -- Shiprock Region -- History; Indian traders -- New Mexico -- Shiprock Region -- History; Shiprock Region (N.M.) -- History; Shiprock Region (N.M.) -- Social life and customs